A PROSES TUBE EXPANSION DAN SEAL WELDING PADA HEAT EXCHANGER - Raihan Shallu Nuralif; Angky Puspawan; Faisal Gumilang (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2026)
This study examines the tube expansion process in heat exchangers at PT IHI Power Service Indonesia using the heavy expand method with a pneumatic expander. As a subsidiary of Japan’s IHI Corporation, the company focuses on repair, maintenance, and fabrication for the power generation industry in Indonesia. The research aims to understand the tube expansion process, the function and operation of the expander tool, and factors that affect work quality and efficiency. The fabrication process includes technical design, material processing, assembly, and component testing. Data were obtained through direct observation, interviews, and technical documentation. Results show that the pneumatic expander improves joint quality and reliability compared to conventional methods. This expansion technique ensures tight connections between tubes and tube sheets, which is essential for heat exchanger performance. The study also highlights the importance of proper torque control and operator training in maintaining process consistency. Overall, the use of pneumatic expansion tools enhances fabrication standards and supports operational efficiency in power plant systems. The findings are expected to contribute to improving productivity at PT IHI Power Service Indonesia and serve as a reference for similar industries focused on heat exchanger fabrication and maintenance.